2021
DOI: 10.1155/2021/6366914
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Integrated Traditional Chinese and Western Medicine in Treating Severe Preeclampsia and Its Influence on Maternal and Infant Outcomes after Cesarean Section under Combined Lumbar and Epidural Anesthesia

Abstract: Objective. This study is aimed to observe the clinical effects of integrated traditional Chinese and Western medicine in treating severe preeclampsia (SPE) and its effects on maternal and infant outcomes after cesarean section under combined lumbar and epidural anesthesia. Method. One hundred and sixty-six pregnant women with SPE were randomly divided into an experimental group and control group, with 83 cases in each group. The control group was given conventional treatments such as magnesium sulfate, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Intercoordination of such two points is most suitable for pain relief. 13 It has been reported in modern medical research that stimulating Hegu and Sanyinjiao acupoints can reinforce adrenal gland activities, increase cortisol secretion and expedite child delivery during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Intercoordination of such two points is most suitable for pain relief. 13 It has been reported in modern medical research that stimulating Hegu and Sanyinjiao acupoints can reinforce adrenal gland activities, increase cortisol secretion and expedite child delivery during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…The results depict that herbal ingredients are effective in treating preeclampsia after childbirth (Gardiner et al 2013;Wang et al 2021). Wang et al 2021, provided a more indepth analysis of the variance between the experimental and control groups' overall clinical successful rates of therapy utilizing herbal medicine, which were 90.36 and 71.08%, respectively (Wang et al 2021).…”
Section: Current Implementation Of Cam Care For Postpartum Pementioning
confidence: 95%
“…The results depict that herbal ingredients are effective in treating preeclampsia after childbirth (Gardiner et al 2013;Wang et al 2021). Wang et al 2021, provided a more indepth analysis of the variance between the experimental and control groups' overall clinical successful rates of therapy utilizing herbal medicine, which were 90.36 and 71.08%, respectively (Wang et al 2021). Iranian researchers Kianpour et al 2016, found that preeclampsia risk factors such maternal stress, anxiety, and postpartum depression can be mitigated by the use of lavender aromatherapy.…”
Section: Current Implementation Of Cam Care For Postpartum Pementioning
confidence: 99%
See 2 more Smart Citations